Molecular profiling to identify relevant immune resistance mechanisms in the tumor microenvironment - Gajewski, Thomas F. (2011)
The molecular identification of tumor antigens initially catalyzed substantial enthusiasm for the development of tumor antigen-based vaccines for the treatment of cancer. However, numerous vaccine approaches in melanoma and other cancers have yielded a low rate of clinical response, despite frequent induction of specific T cells as detected in the peripheral blood. This observation has prompted several investigators to begin interrogating the tumor microenvironment for biologic correlates to tumor response versus resistance. Evidence is beginning to emerge suggesting that distinct subsets of tumors may exist that reflect distinct categories of immune escape. Lack of chemokine-mediated trafficking, poor innate immune cell activation, and the presence of specific immune suppressive mechanisms can be found to characterize subsets of tumors. A non-inflamed tumor phenotype may predict for resistance to cancer vaccines, suggesting a possible predictive biomarker and patient enrichment strategy. But in addition, characterization of these subsets may pave the way for catering therapeutic interventions toward the biologic features of the tumor in individual patients.